2015
DOI: 10.2340/16501977-1914
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation provided to patients with rheumatoid arthritis: A comparison of three different rheumatology clinics in Austria, Sweden and the UK from the perspectives of patients and health professionals

Abstract: Integration of patients' and health professionals' views on how rehabilitation services are coordinated and how (parts of) processes are set up elsewhere provide valuable information for the further optimization of rehabilitation services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In recent decades, many countries around the world have been developing the system of medical rehabilitation aimed at restoration of functional ability and quality of life to those with physical impairments, as well as their maximal integration or reintegration in society and prevention of disability [8][9][10][11][12]. It should be noted that each country arranges the system of medical rehabilitation according to its national requirements.…”
Section: Review and Discussionmentioning
confidence: 99%
“…In recent decades, many countries around the world have been developing the system of medical rehabilitation aimed at restoration of functional ability and quality of life to those with physical impairments, as well as their maximal integration or reintegration in society and prevention of disability [8][9][10][11][12]. It should be noted that each country arranges the system of medical rehabilitation according to its national requirements.…”
Section: Review and Discussionmentioning
confidence: 99%
“…It is reported that heritability of RA was ranging from 15 to 60%, indicating genetic factor as one of the pathogenic factors [2]. In addition, a variety of environmental factors, immune cells and cytokines, such as smoking, T cells, B cells, TLRs (Toll-like receptor) and virus are involved in the pathological process [3][4][5].…”
Section: Introductionmentioning
confidence: 99%